Laparoscopic ureterolysis with simultaneous ureteroscopy and percutaneous nephroscopy for treating complex ureteral obstruction after failed endoscopic intervention: A technical report - Zhixiang Wang; Bing Liu; Xiaofeng Gao; Yi Bao; Yang Wang; Huamao Ye; Yinghao Sun; Linhui Wang (Asian Journal of Urology)
Objective: Complex ureteral obstruction is refractory to conventional urological intervention. This report describes a case of laparoscopic ureterolysis with simultaneous ureteroscopy and percutaneous nephroscopy for treating complex ureteral obstruction. Methods: Right-side multiple ureteral stones and complicating ureteral obstruction failed an initial attempt of ureteroscopy lithotripsy with simultaneous percutaneous nephroscopy in a 23-year-old male. Laparoscopic ureterolysis with ureteroscopy and percutaneous nephroscopy was used simultaneously to dissect the periureteral adhesions with the patient placed in the Galdakao-modified supine Valdivia position. The ureter was incised to allow the insertion of a ureteral catheter through the twisted ureter, and a guide wire was advanced into the pelvis using ureteroscopy. A double-J stent was placed into the right-side ureter using antegrade percutaneous nephroscopy. Results: The laparoendoscopic procedure lasted 330 min with an estimated bleeding volume of 100 mL. The patient underwent an uneventful postoperative course, and postoperative follow-up radiography confirmed good positioning of the double-J stent. The double-J stent was removed 3 months after operation. The patient remained asymptomatic within a 13-month follow-up period. Conclusion: Laparoscopic ureterolysis with simultaneous ureteroscopy and percutaneous nephroscopy is an effective and safe treatment option for complex ureteral obstruction.